Pembelajaran Fikih Humanistik Program M2KD untuk Moderasi Beragama Santri Mambaul Ulum Pamekasan - Ach. Sayyi; Afandi; Imaniyatul Fithriyah; Masrufah (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
This study examines the humanistic and moderate-oriented model of classical fiqh learning in the M2KD Program at Pesantren Mambaul Ulum Bata-Bata Pamekasan. Using a qualitative case study approach, data were collected through observation, interviews, and document analysis. Findings reveal four key points: (1) humanistic values emerge through egalitarian, dialogical, and reflective learning; (2) fiqh instruction applies an accelerative, multi-level strategy based on the zone of proximal development; (3) moderation is fostered through discursive methods emphasizing tasamuh, ta‘adul, and tawazun; and (4) M2KD integrates classical text mastery with inclusive character formation. This model balances tradition and contemporary relevance.